The Politics of Europeanization 2003
DOI: 10.1093/0199252092.003.0002
|View full text |Cite
|
Sign up to set email alerts
|

The Europeanization of Public Policy

Abstract: This chapter deals with the Europeanization of public policy, with emphasis on the problems that researchers encounter when they try to get to grips with the concept of Europeanization, the issue of explanation, the measurement of effects and the control of alternative rival hypotheses. It covers the domestic impact of the public policy of the European Union (EU), for which the term ‘EU-ization’ could be used. Featherstone has shown in the introductory chapter that the scope of Europeanization can go beyond EU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
301
0
45

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 702 publications
(349 citation statements)
references
References 27 publications
3
301
0
45
Order By: Relevance
“…Our analysis is informed by O'Donnell's (1994) conceptualization of delegative democracy, supplemented by literature on economic and political reform in Europe (e.g. Dyson & Goetz, 2003;Featherstone & Papadimitriou, 2008;Radaelli, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our analysis is informed by O'Donnell's (1994) conceptualization of delegative democracy, supplemented by literature on economic and political reform in Europe (e.g. Dyson & Goetz, 2003;Featherstone & Papadimitriou, 2008;Radaelli, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the implementation of EU-inspired reforms by member states is often associated with significant gaps between the intended purposes and the actual effects of the Europeanization project (Featherstone & Papadimitriou, 2008;Radaelli, 2003). In a sense, when change is imposed from above (Mouzelis, 1995), the complex, multifaceted and interdependent domestic system of economic and political power illustrates a form of social "homeostasis" (Simon, 1962, p. 467).…”
Section: Obs Within the Ssc Systemmentioning
confidence: 99%
“…(Radaelli 2003, 30) In an exploratory manner, it seeks to capture the extent of diffusion and institutionalisation of the practices of interest intermediation, defined at the EU level and sent to the member states in the form of legal or normative requirements, with a view to identifying the degree of "incorporation" as put by Radaelli (2003). The principal point of departure is the assumption that the partnership principle communicates a specific idea or a mode of state-society relations imposed by the EU.…”
Section: Introductionmentioning
confidence: 99%
“…This has been described in terms of 'Europeanization', i.e. the process of constructing, diffusing and implementing formal and informal norms, which are first defined within the EU and then incorporated in domestic discourse, identity and political structures (Radaelli, 2003). The literature on 'external governance', i.e.…”
Section: Conclusion: Europe At the Crossroads Of Hope And Disillusionmentioning
confidence: 99%